Indian knowledge system-IV:indian science, engineering & technology (past,present & future) - Sarkar, Anindita (Taurean Pub, 2025)
Indian knowledge system-IV:indian science, engineering & technology (past,present & future) / Sarkar, Anindita. -- Kolkata: Taurean Pub., 2025 001.954 Sa245 No. of Copies : 1